ANALISIS KEMAMPUAN BERHITUNG PEMBELAJARAN MATEMATIKA PADA KURIKULUM MERDEKA KELAS II SDN 03 KERANGAN PURUN - Anggel Jendera; Septian Peterianus (STKIP Subang, 2026)
This study aims to analyze the numeracy skills of second-grade students at SDN 03 Kerangan Purun in mathematics learning based on the Independent Curriculum. The research method used was qualitative with a descriptive approach and a case study design. The study subjects consisted of 13 second-grade students, including 8 boys and 5 girls. Data collection techniques were conducted through observations using a Likert scale, semi-structured interviews with teachers and students, and documentation. The results showed that the distribution of students' numeracy skills varied, with 61.5% of students falling into the